Menganalisa Paradigma Kesatuan Ilmu di UIN Walisongo Semarang - Aula Dwi Zahrani; Khusnia Wildan; Muhammad lutfi Adisty; Nasikhin Nasikhin; Mahfud Junaedi; Pei-Zhuang Wang (-, 2023)
This study aims to analyze the paradigm of unity of science at UIN Walisongo. By using literature methods, this study shows that, 1. The definition of the unity of science paradigm at Uin Walisongo contains the meaning that in fact science is a unity that comes from God and leads to God, through His revelation both directly and indirectly. 2. The principles of the unified science paradigm at UIN Walisongo itself have five principles, namely: integration, collaboration, dialectics, prospective, and pluralistic. 3. The unified science paradigm strategy at UIN Walisongo has a very ambitious vision, they are committed to being not just a an educational institution, but also a center of excellence in research and development. 4. The aim of the UIN Walisongo paradigm is to unify religion and science and also complete the paradigm where science is considered everything, thereby ignoring other aspects, including humanity. This study has had a positive impact on the development of philosophical science, especially in the study of the paradigm of scientific unity at UIN Walisongo. Our analysis can be used to strengthen the argument that the thinking of western philosophers can actually coexist with Islamic philosophy.